Dynamics of the base of ribosomal A-site finger revealed by molecular dynamics simulations and Cryo-EM - Réblová, Kamila; Rázga, Filip; Li, Wen; Gao, Haixiao; Frank, Joachim; Sponer, Jirí (Nucleic acids research, 2010)
Helix 38 (H38) of the large ribosomal subunit, with a length of 110 A, reaches the small subunit through intersubunit bridge B1a. Previous cryo-EM studies revealed that the tip of H38 moves by more than 10 A from the non-ratcheted to the ratcheted state of the ribosome while mutational studies implicated a key role of flexible H38 in attenuation of translocation and in dynamical signaling between ribosomal functional centers. We investigate a region including the elbow-shaped kink-turn (Kt-38) in the Haloarcula marismortui archaeal ribosome, and equivalently positioned elbows in three eubacterial species, located at the H38 base. We performed explicit solvent molecular dynamics simulations on the H38 elbows in all four species. They are formed by at first sight unrelated sequences resulting in diverse base interactions but built with the same overall topology, as shown by X-ray crystallography. The elbows display similar fluctuations and intrinsic flexibilities in simulations indicating that the eubacterial H38 elbows are structural and dynamical analogs of archaeal Kt-38. We suggest that this structural element plays a pivotal role in the large motions of H38 and may act as fulcrum for the abovementioned tip motion. The directional flexibility inferred from simulations correlates well with the cryo-EM results.
Keywords: Potassium Chloride; RNA, Ribosomal, 23S; Thermus thermophilus; simulace molekulární dynamiky; chlorid draselný; Nucleic Acid Conformation; Cryoelectron Microscopy; Deinococcus; velké podjednotky ribozomu archebakteriální; Molecular Dynamics Simulation; sodík; Escherichia coli; RNA ribozomální 23S; Sodium; konformace nukleové kyseliny; elektronová kryomikroskopie; velké podjednotky ribozomu bakteriální; Ribosome Subunits, Large, Bacterial; Haloarcula marismortui; Ribosome Subunits, Large, Archaeal